2013
DOI: 10.1124/jpet.113.203448
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe Increases Hepatic Iron Levels in Mice Fed a High-Fat Diet

Abstract: Accumulating evidence suggests that ezetimibe may be a promising agent for treatment of nonalcoholic fatty liver disease and steatohepatitis (NAFLD/NASH). Phlebotomy and dietary iron restriction reduce serum transaminase in NAFLD/NASH patients. Recent studies have shown that a mutual effect exists between lipid metabolism and iron metabolism. Accordingly, we examined the effect of ezetimibe on iron metabolism in mice fed a high-fat diet with or without iron. We fed C57BL/6 mice the following diets for 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Our results demonstrated that insulin therapy effectively released HIO, manifested by the recovery of liver iron content and serum ferritin and the improvement tendency of serum sTfR, and lowered serum iron to normal level in STZ-induced both type 1 and type 2 diabetic rats. In addition, simple HFD induction that led to IR but did not elevate fasting blood glucose had no influence on liver or serum iron, which was not reported in other studies (23,33). These findings suggest that body iron homeostasis may be closely related to insulin signaling.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Our results demonstrated that insulin therapy effectively released HIO, manifested by the recovery of liver iron content and serum ferritin and the improvement tendency of serum sTfR, and lowered serum iron to normal level in STZ-induced both type 1 and type 2 diabetic rats. In addition, simple HFD induction that led to IR but did not elevate fasting blood glucose had no influence on liver or serum iron, which was not reported in other studies (23,33). These findings suggest that body iron homeostasis may be closely related to insulin signaling.…”
Section: Discussionmentioning
confidence: 42%
“…Insulin supplementation eliminated these abnormal changes in STZ and HFD+STZ rats, indicating that hepcidin, which negatively regulates Fpn and iron absorption and restricts the level of serum iron, may be positively regulated by insulin. It was also found in other HFD rat models that hepcidin expression remained unchanged (33,38) or began decreasing only when fasting blood glucose was increased (39). Clinical studies (16,17,34) showed that the prohepcidin or hepcidin level in blood was significantly decreased in DM2 patients with hyperferritinemia.…”
Section: Discussionmentioning
confidence: 86%
“…Insulin resistance or impaired insulin signaling is a main contributor to the disruption of glucose metabolism and plays a pivotal role in pathogenesis of T2DM ( 47 , 48 ). Reciprocally, the improvement or restoration of insulin signaling is an effective treatment for restoring abnormal glucose metabolism in T2DM ( 49 ). In this study, we found that MARCKS deficiency increased glucose levels in serum and accelerated insulin resistance in HF diet-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic steatosis, induced by a high-fat diet, but not a high-fructose diet, was inhibited by ezetimibe administration (8). It has also been reported that hepatic iron levels in mice fed a high-fat diet are increased following treatment with ezetimibe (9). Despite these notable findings, mechanisms by which ezetimibe administration ameliorates hepatic steatosis, insulin resistance and obesity remain largely unexplored.…”
Section: Introductionmentioning
confidence: 98%